2019
DOI: 10.1002/cbm.2117
|View full text |Cite
|
Sign up to set email alerts
|

Mentally disordered offenders discharged from designated hospital facilities under the medical treatment and supervision act in Japan: Reoffending and readmission

Abstract: Background Current Japanese forensic mental health legislation (Medical Treatment and Supervision Act [MTSA]) was enacted in 2003. Little is known, however, about the actual outcomes for the offender patients detained within hospitals under this provision. Aim This study aimed to quantify reoffending and readmission following patients' discharge from forensic psychiatric hospital units across Japan and explore related risk factors. Methods We followed up 526 offenders with mental disorder who had been detained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Six studies reported on surveys assessing the performance of community-based mental health care on the ACT, compulsory treatment, home-visit nursing care, physical complications, and a welfare medicine collaboration on a remote island [ 14 , 15 , 16 , 17 , 18 , 19 ]. One article reported on two sets of results obtained using two different research designs [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported on surveys assessing the performance of community-based mental health care on the ACT, compulsory treatment, home-visit nursing care, physical complications, and a welfare medicine collaboration on a remote island [ 14 , 15 , 16 , 17 , 18 , 19 ]. One article reported on two sets of results obtained using two different research designs [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Past studies have found that the total cumulative rate of reoffending after discharge was 2.5% (1.1–3.9%) at 1 year and 7.5% (4.6–10.4%) at 3 years. The rate of serious reoffending was 0.4% (0.18–0.99%) at 1 year and 2.0% (0.4–3.6%) at 3 years ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, a short term was required, as START was deliberately developed to assess short-term risk and treatability. Second, the period of follow-up had to be long enough for incidents to occur, as a past study showed that the rate of reoffending within 1 year after discharge was <3% among MTSA patients ( 17 ), and cosiderably low rate. Therefore, it was assumed better to follow up for 6 months rather than three, in order to increase the chance of collecting negative incident data.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, studies based on empirical recidivism have also established a relationship between recidivism and substance use or dependence disorders (Honegger & Honegger, 2020;Nagata et al, 2019;Walsh et al, 2020;Wilton & Stewart, 2017), as well as with other psychic pathologies when such disorders are comorbid (Calvo et al, 2016;Cappai et al, 2017;Weizmann-Henelius et al, 2019). Specifically, several studies relate personality disorders to future incarceration (Calvo et al, 2016), even specifying the type of disorder (Martin et al, 2019;Walsh et al, 2020;Weizmann-Henelius et al, 2019), associating recidivism with antisocial personality disorder.…”
Section: Introductionmentioning
confidence: 99%